Scattering and stress concentration of SH guided waves by a semicircular hole on the boundary of an infinite piezoelectric ceramic plate - Qu, Enxiang; Qi, Hui; Guo, Jing; Liu, Shuang; Li, Ying (Frontiers in Physics, 2025)
In this paper, the dynamic issue related to a semicircular depression in a piezoelectric ceramic plate is investigated. The fundamental mechanical problems of dynamic stress concentration factor and electric field intensity concentration factor are addressed using the complex function approach, wave function expansion method, and repeated mirror method, and the analytical expressions for the relevant stress concentration are presented. The influences of the dimensionless parameter wave number, strip thickness, and guided wave order on the stress concentration of the SH guided wave incident within the strip are explored.The results indicate that, with a fixed plate thickness, the 0 order high frequency guided wave exerts a more pronounced influence on the stress concentration near the hole, resulting in more severe damage. Under the electromechanical coupling effect, the detrimental impact of the electric field far exceeds that of the stress field. Consequently, it is essential to focus on the adverse effects imposed by the electric field.